Confined Nystatin Polyenes in Nanopore Induce Biologic Ionic Selectivity. (14th June 2016) - Boukari, Khaoula; Paris, Guillaume; Gharbi, Tijani; Balme, Sébastien; Janot, Jean-Marc; Picaud, Fabien
Abstract : Antifungal polyenes such as nystatin (or amphotericin B) molecules play an important role in regulating ions permeability through membrane cell. The creation of self-assembled nanopores into the fungal lipid membranes permits the leakage and the selectivity of ions (i.e., blockage of divalent cations) that cause the cell death. These abilities are thus of first interest to promote new biomimetic membranes with improved ionic properties. In the present work, we will use molecular dynamic simulations to interpret recent experimental data that showed the transfer of the nystatin action inside artificial nanopore in terms of ion permeability and selectivity. We will demonstrate that nystatin polyenes can be stabilized in a hydrophobic carbon nanotube, even at high concentration. The high potential interaction between the polyenes and the hydrophobic pore wall ensures the apparition of a hole inside the biomimetic nanopore that changes its intrinsic properties. The probability ratios of cation versus anion show interesting reproducibility of experimental measurements and, to a certain extent, opened the way for transferring biological properties in synthetic membranes.